MENTORING PROGRAM: Empowerment and Human Resources Development - Afandi, Ahmad (Perhimpunan Sarjana Ekonomi dan Bisnis, 2021)
The need for quality employees is a necessity, this is believed to be able to help the company in achieving its goals. In fact, the highest quality employees can drive rapid progress and help companies stand out from competition and global business threats. Based on this, the company is aware of an effort to develop employees in the right way, namely through mentoring or mentoring programs. This study aims to identify, analyze, and suggest how to develop employees well through a mentoring program. To answer this goal, a qualitative scientific method was used. Data and information were obtained through observation and interviews with employees of Hutama Karya companies who participated in the mentoring program. While the analytical method using descriptive technique. The results of the study show that mentoring programs can help employees accelerate their abilities and increase better opportunities. The interesting thing about this program is that the company has an effective leadership regeneration system, so that it can help maintain the company's existence in the future